Creating French-style pension funds: Business, labour and the battle over patient capital - Naczyk, M (SAGE Publications, 2016)
European governments are increasingly retreating from public pension provision and promoting the expansion of private pension funds. Analysts of comparative social policy have traditionally considered that the politics of pension privatisation is driven by politicians’ and socioeconomic actors’ concerns about the generosity and costs of pension arrangements. But, when they are fully funded instead of being financed on a pay-as-you-go basis, pensions generate funds that are injected into the financial system. The existence of such a welfare–finance nexus means that stakeholders in the pension system are also attentive to how pension funds invest their assets, and may try to actively shape the institutional design of pensions in accordance with such financial concerns. This article focuses on the role of organised labour and business, that is, employers and the financial industry, in pension privatisation and develops theoretical expectations on how these actors’ interest in maximising control over private pension funds’ financial assets affects pension politics. The argument is tested with a case study of French pension privatisation between the 1980s and the 2000s.